Rancang Bangun Aplikasi Penilaian Pelayanan Desa di Kantor Lurah Sei Agul Menggunakan Metode Service Quality - Silalahi, Vina Aulia; Nidia Enjelita Br. Saragih (Universitas Methodist Indonesia, 2025)
Public services at the village office play a crucial role in creating an efficient, transparent government focused on public satisfaction. However, many residents are still dissatisfied with the services provided, both in terms of speed, accuracy, and the attitude of officers. Therefore, a system is needed that not only makes it easier for the public to request services but also allows for objective assessment of service quality. This study aims to design and build a mobile-based application that facilitates service requests and service assessments by the public. In the assessment, the Service Quality (ServQual) method is used, which measures the gap between public expectations and perceptions across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The result of this study is an Android-based application for accessing village services and providing input to the village office in continuously improving service quality.